Effects of EGCG on the Mobilization of Mineral Elements from Tea Plantation Soil. Issue 16 (8th September 2021) - Huang, Danjuan; Gong, Ziming; Wang, Youping; Chen, Xun; Tan, Rongrong; Wang, Hongjuan; Mao, Yingxin
ABSTRACT: Tea polyphenols (TPs) may reach the soil through root secretions and the decomposition of fallen leaves in the tea garden ecosystem and may activate elements existing in the soil through complexation. We designed different epigallocatechin gallate (EGCG) concentration, residence time, and extraction reagent to determine the effect of these treatments on the mobilization of potassium (K), calcium (Ca), magnesium (Mg), iron (Fe), and manganese (Mn). The results showed that the EGCG concentration had a significant impact on the mobilization of these five elements. According to the correlation coefficient of desorptive kinetic equations, K, Ca, Mg, Fe, and Mn desorption onto soil was well described by first-order kinetic equation model (R 2  > 0.98, P < .01). The effect of LMWOAs (low molecular weight organic acids) was greater than that of EGCG on mobilizing amounts of large elements including K, Ca, and Mg. Our study provides a more detailed understanding of the interactions between EGCG and minerals, which may offer prospects for improving plant nutrient acquisition through direct modifications of rhizosphere management.